Intracerebral haemorrhage after the neonatal period. Issue 6 (June 1986) - Livingston, J H; Brown, J K
Abstract : Intracerebral haemorrhage is rare in childhood. We have reviewed the last 10 years' experience, in our referral area, of parenchymatous intracerebral haemorrhage in children from 1 month to 16 years of age. There were 27 cases, five of which were intracerebellar and two predominantly intraventricular. The commonest aetiology was vascular malformation (10), followed by haemorrhage into tumour (four), and coagulopathies (five). Clinical features were non-specific, but altered consciousness, headache, vomiting, and focal signs were the most common. Focal signs were, however, rare in the patients with intracerebellar haemorrhage. There was an overall mortality of 54% (14 out of 27). Nine patients were handicapped on follow up, but none severely so. For the diagnosis of intracerebral haemorrhage a high level of clinical suspicion is needed with early use of computed tomography. Maintenance of homeostasis, relief of raised intracranial pressure, and evacuation of haematoma are the aims of management.